Karakterisasi mikrostruktur film whey dengan penambahan konjac glucomannan - Fahrullah Fahrullah; Mohamad Ervandi (AGROINTEK, 2022)
The research aims to observe the effect of konjac glucomannan and different types of plasticizers on the microstructure of whey film. The microstructure of whey film was investigated using an experimental method. The research was conducted in descriptive methods with two treatments.The treatment used konjac glucomannan concentration (P4= 2.5 %; P7= 3 %) and different types of plasticizers (C1= glycerol 30 %; polyethylene glycol 30 %). The results showed that the combination of whey and konjac glucomannan had an effect on the microstructure of the film. The addition of konjac glucomannan concentration, 30 % glycerol, and 30 % PEG plasticizers gave microstructural characteristics with good whey film surface. The microstructure of this film was determined during the heating, drying process and the contribution of the gel from konjac glucomannan to the whey film structure. A more homogeneous edible film microstructure was obtained using a 2.5 % concentration of KGM with the use of 30 % glycerol plasticizer where the distribution of konjac glucomannan was mixed into the whey protein matrix evenly (homogeneous).